Graduate nurse practice readiness: A conceptual understanding of an age old debate. Issue 4 (August 2017) - El Haddad, May; Moxham, Lorna; Broadbent, Marc
Abstract: The growing demands of an aging population, a looming nursing shortage, widespread fiscal constraints and the growing complexity of a dynamic healthcare landscape means that graduate registered nurses (GRNs) are increasingly expected to be practice ready. This term, also known as fitness to practice, has long been used to describe a concept that is actually unformulated. Indeed, what does being practice ready actually mean and who are the appropriate stakeholders to define it? The prevalence of the ongoing debate about practice readiness, which has now been around for decades, indicates the issue is still at the fore of nursing discourse. Such debate is partly reflective of a difference in opinion between nurses in education and those within clinical practice sectors, as to whether new GRNs are in fact practice ready. This paper describes the findings of a grounded theory (GT) study, which examined the notion of practice readiness from the perspective of Nurse Unit Managers (NUMs) from the acute care practice sector and Bachelor of Nursing Program Coordinators (BNPCs) within the Australian context. Semi-structured interviews were undertaken with sixteen BNPCs and NUMs from across the country. Findings suggest that as a result of contextual influences and varying system drivers, BNPCs and NUMs in Australia inhabit disparate realities. When it comes to practice readiness, these cohorts view new graduates through different lenses and as such, have different perspectives and expectations of what it means to be practice ready. Practice readiness is indeed a nebulous concept. There is no clear definition and the concept means different things to different people. These findings have implications for policy, education and practice to consider a new world where all stakeholders involved in preparing the future nursing workforce have an equal say and a shared understanding of what practice readiness means.